Penggunaan Sidik Jari Pada Proses Penyidikan Tindak Pidana (Studi di Kepolisian Resort Jember) - Putri Aprilia, Lintang Tiara; Halif, Halif; Wildana, Dina Tsalist (Pusat Penelitian dan Pengembangan Polri, 2024)
Fingerprints serve as scientific evidence or material evidence due to their uniqueness, which cannot be discerned with the naked eye. They play a critical role in providing information about evidence. The Indonesian National Police's specialized team, known as INAFIS, supports the investigative process, particularly in fingerprint identification. This research aims to explore the function of fingerprint evidence in obtaining other forms of evidence for suspect determination. Additionally, it seeks to uncover investigative efforts despite limitations in evidence collection during the investigation process. This research method uses a case approach, namely an approach carried out by analyzing and examining cases related to the legal issues being faced. The findings indicate that fingerprints not only aid in developing and discovering other evidence but also serve as initial clues in criminal cases. Furthermore, fingerprints can be used to identify unidentified victims. Ultimately, this contributes to the continuity of justice, extending all the way to the courtroom.